Bidding behavior in the longer term refinancing operations of the European Central Bank: Evidence from a panel sample selection model - Linzert, Tobias; Nautz, Dieter; Bindseil, Ulrich (Journal of Banking & Finance, 2007)
This paper analyzes individual bidding data of the longer term refinancing operations (LTROs) of the European Central Bank. We investigate how banks’ bidding behavior is related to a series of exogenous variables including collateral costs, interest rate expectations, market volatility and to individual bank characteristics like country of origin, size, and experience. A specific feature of these auctions is that the number and composition of bidders varies over time. Therefore, we estimate panel sample selection models to control for a bank’s endogenous participation decision. We find that bidding strategies depend on the banks’ attributes. Yet, different bidding behavior generally does not translate into differences concerning bidder success. There is evidence for the winner’s curse effect in LTROs indicating a common value component in banks’ demand for longer term refinancing.